Beastie Boys - Video Anthology - Hörnblowér, Nathanial; Perez, David; Jonze, Spike (The Criterion Collection, 2000)
Augmenting 18 videos with more than 100 camera angles and remixes old and new, the 2-disc set brings Criterion's attention to detail and quality to bear on some of the most hilarious and visually creative music clips ever. [www.amazon.com]